Occupational exposure to diesel engine exhaust and serum levels of microRNAs in a cross‐sectional molecular epidemiology study in China. (1st March 2023) - Hu, Wei; Wong, Jason Y. Y.; Dai, Yufei; Ren, Dianzhi; Blechter, Batel; Duan, Huawei; Niu, Yong; Xu, Jun; Fu, Wei; Meliefste, Kees; Zhou, Baosen; Yang, Jufang; et al.
Abstract: Diesel engine exhaust (DEE) is an established lung carcinogen, but the biological mechanisms of diesel‐induced lung carcinogenesis are not well understood. MicroRNAs (miRNAs) are small noncoding RNAs that play a potentially important role in regulating gene expression related to lung cancer. We conducted a cross‐sectional molecular epidemiology study to evaluate whether serum levels of miRNAs are altered in healthy workers occupationally exposed to DEE compared to unexposed controls. We conducted a two‐stage study, first measuring 405 miRNAs in a pilot study of six DEE‐exposed workers exposed and six controls. In the second stage, 44 selected miRNAs were measured using the Fireplex circulating miRNA assay that profiles miRNAs directly from biofluids of 45 workers exposed to a range of DEE (Elemental Carbon (EC), median, range: 47.7, 6.1–79.7 μg/m 3 ) and 46 controls. The relationship between exposure to DEE and EC with miRNA levels was analyzed using linear regression adjusted for potential confounders. Serum levels of four miRNAs were significantly lower (miR‐191‐5p, miR‐93‐5p, miR‐423‐3p, miR‐122‐5p) and one miRNA was significantly higher (miR‐92a‐3p) in DEE exposed workers compared to controls. Of these miRNAs, miR‐191‐5p ( p trend  = .001, FDR = 0.04) and miR‐93‐5p ( p trend  = .009, FDR = 0.18) showed evidence of an inverse exposure–response with increasing EC levels. Our findings suggest that occupational exposure to DEE may affect circulating miRNAs implicated in biological processes related to carcinogenesis, including immune function.